{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

# ex13_9b - ra=-k1*x(1*x(2-k2*x(1 rc=k1*x(2*x(1...

This preview shows page 1. Sign up to view the full content.

% "ex13_9b" % m-file to solve example 13.9 Part 2 % % x(1)=ca % x(2)=cb % x(3)=cc % x(4)=F % x(5)=cd % x(6)=ce % xdot(1)=d(ca)/dz, xdot(2)=d(cb)/dz, etc. % function xdot=ex13_9(z,x) f cao=1; cbo=1; cco=0; cdo=0; ceo=0; lam=6-z; k1=1; k2=1; k3=1; E1=0.47219*lam^4-1.30733*lam^3+0.31723*lam^2+0.85688*lam+0.20909; E2=3.83999*lam^6-58.16185*lam^5+366.20970*lam^4-1224.66963*lam.^3+2289.84857*lam^2- 2265.62125*lam+925.46463; E3=0.0041*lam^4-0.07593*lam^3+0.52276*lam^2-1.59457*lam+1.84445;
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: ra=-k1*x(1)*x(2)-k2*x(1); rc=k1*x(2)*x(1); rb=-k1*x(1)*x(2)-k3*x(2)*x(5); rd=k2*x(1)-k3*x(2)*x(5); re=k3*x(2)*x(5); r if lam <=1.82 E=E1; elseif lam <=2.8 E=E2; else E=E3; end e EF=E/(1-x(4)); E xdot(1,:)=-(-ra+(x(1)-cao)*EF); xdot(2,:)=-(-rb+(x(2)-cbo)*EF); xdot(3,:)=-(-rc+(x(3)-cco)*EF); xdot(4,:)=-E; xdot(5,:)=-(-rd+(x(5)-cdo)*EF); xdot(6,:)=-(-re+(x(6)-ceo)*EF);...
View Full Document

{[ snackBarMessage ]}